Atividade anti-inflamatória e neuroprotetora da fração de Aspidosperma pyrifolium rica em derivado glicosilado do ácido salicílico - Araujo, Dayane Pessoa (2017)
Parkinson's disease (PD) is characterized by the progressive and slow degeneration of the neurons of the substantia nigra causing the reduction of dopamine (DA) in the striatum. Since inflammation is involved in the pathogenesis of PD and Aspidosperma pyrifolium Mart it presents therapeutic anti-inflammatory potential, the present study investigated the toxic, anti-inflammatory and neuroprotective effects of the aqueous fraction of the ethanolic extract of the seeds of Aspidosperma pyrifolium Mart. (APSE-Aq). Initially, preliminary oral acute toxicity should be investigated by hippocratic screening (10, 100, 500 and 1000mg/kg, o.u.). The antioxidant potential of APSE-Aq (10, 25, 50, 100 and 200 μg/mL) was assessed by in vitro assays using the DPPH radical sequestering ability and as standard the vitamin E (50 μg / mL); and the oxidative metabolism of activated neutrophils with PMA by the chemiluminescence assay using luminol and lucigenin probes, the groups with composition by APSE-Aq (0,1, 1, 10, 20 and 50 μg/mL) and as standard quercetin (50 μg/mL). The anti-inflammatory activity was tested by 1% carrageenan-induced paw edema (50,100 and 200mg/kg o.u). A neuroprotective activity was investigated through the PD model using 6-hydroxydopamine (6-OHDA) in the right striatum of male Wistar rats and treated with APSE-Aq (100 and 200mg/kg o.u.) for 14 days after injury. The APSE-Aq did not cause the death of animals. Signs of toxicity were observed, especially in the dose of 1000mg observed in the hippocratic screening, such as: analgesia, anesthesia, cyanosis and hypnosis presented. APSE-Aq presented a sequestering ability of the DPPH radical, as well as modulated the oxidative metabolism of neutrophils by acting on the MPO-H2O2-HOCl system and reducing O2- production. No paw edema by carrageenan, APSE-Aq showed anti-inflammatory activity, as well as reduced immunoreactivity for TNF-α. In the PD model, motor activity improvement was observed through a reduction in apomorphine-induced rotations, increase in locomotor activity and rearing in the open field test, contralateral leg use without cylinder test and reduction of rotarod falls. APSE-Aq reduced lipid peroxidation and nitrite/nitrate in the prefrontal cortex (PFC), hippocampus (HC) and striatum (S), increased DA and DOPAC content and reduced GABA and glutamate in S. An immunoreactivity for tyrosine hydroxylase and dopamine transporter was reduced and increased TNF-α in the 6-OHDA group with respect to the group injured and treated with APSE-Aq. Our results suggest that APSE-Aq has a potential neuroprotective effect and this effect is possibly related to its antioxidant and anti-inflammatory capacity, which makes the species a potential alternative therapeutic target for Parkinson's disease.